The Link Between Agricultural Budgetary Allocation and Economic Growth in Nigeria - Kareem, Salami Dada; Olusegun, Atoyebi Kehinde; Arogundade, Lawal Samad (International Journal of Business, Economics and Management, 2017)
This study investigates the nexus between Agricultural budgetary allocation and Economic Growth in Nigeria by employing simple regression analysis and a further test of cointegration and vector error correction model to determine short run dynamic behaviour of the variable. The result of the study revealed that there is positive relationship between Agricultural budgetary allocation and Economic Growth in the long run. It was also observed that since the Agricultural budgetary allocation and Economic Growth are positively related. This relationship is significant over the two years lagged value of budgetary allocation to Agriculture. And by implication, the government has to stand aloof by increasing expenditure on agriculture because agricultural sector plays a vital role towards the National Transformation in Nigeria.